Hydrothermal liquefaction of various biomass and waste feedstocks for biocrude production: A state of the art review. (February 2017) - Dimitriadis, Athanasios; Bezergianni, Stella
Abstract: The continuing use of fossil fuels accelerated the energy crisis, environmental pollution, and global warming in recent years. These problems are the driving force of the worldwide search for new alternative energy, among which biomass is considered to be one of the most promising candidates due to its renewable, carbon neutral and high productivity characteristics. Hydrothermal liquefaction (HTL) is an alternative technology of exploiting different types of biomass for fuels production, involving the direct biomass conversion to liquid, in the presence of a solvent and in some times catalyst. HTL has undergone a sudden increase in the number of publications in recent years. The wide variation in different types of feedstock tested, their initial state, the reaction conditions and/or the catalysts applied renders a wide but rather fragmentary spectrum of knowledge generated. This review is a summary of state-of-the-art knowledge of HTL for various feedstocks such as woody biomass, wastes, plastics and microalgae.